2015
DOI: 10.1111/boc.201400077
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillarin from Archaea to human

Abstract: Fibrillarin is an essential protein that is well known as a molecular marker of transcriptionally active RNA polymerase I. Fibrillarin methyltransferase activity is the primary known source of methylation for more than 100 methylated sites involved in the first steps of preribosomal processing and required for structural ribosome stability. High expression levels of fibrillarin have been observed in several types of cancer cells, particularly when p53 levels are reduced, because p53 is a direct negative regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 89 publications
(125 reference statements)
2
101
0
Order By: Relevance
“…Fib2 can be divided into four regions according to sequence characteristics (Rodriguez-Corona et al, 2015), with one region containing the glycine-arginine-rich (GAR) domain functioning in interactions with various viral proteins (VPs) (Kim et al, 2007b;Semashko et al, 2012). Therefore, the Fib2, GAR domain and a truncation mutant (Fib2 ᭝GAR ) were cloned into E. coli cells and purified.…”
Section: Fib2 Is Involved In Bsmv Cell-to-cell Movementmentioning
confidence: 99%
“…Fib2 can be divided into four regions according to sequence characteristics (Rodriguez-Corona et al, 2015), with one region containing the glycine-arginine-rich (GAR) domain functioning in interactions with various viral proteins (VPs) (Kim et al, 2007b;Semashko et al, 2012). Therefore, the Fib2, GAR domain and a truncation mutant (Fib2 ᭝GAR ) were cloned into E. coli cells and purified.…”
Section: Fib2 Is Involved In Bsmv Cell-to-cell Movementmentioning
confidence: 99%
“…In addition to RNA processing, fibrillarin is implicated in DNA damage, abiotic stress, apoptosis, chromatin remodeling, and transcription mechanism. Moreover, to a large extent, its functional diversity is conferred upon by its interacting partner (Rodriguez‐Corona et al ., ). Thus far, physiological functions of fibrillarin in plants are poorly understood.…”
Section: Discussionmentioning
confidence: 97%
“…It is mainly located in the fibrillar center and dense fibrillar component region of the nucleoli, where it is directly involved in several steps of ribosome biogenesis. Besides pre‐ribosomal RNA (rRNA) processing, fibrillarin is implicated in several cellular processes, including oncogenesis, viral progression, apoptosis, chromatin remodeling, basal transcription assembly, and transcription initiation, suggesting it is active in subcellular locations other than the nucleoli (Rodriguez‐Corona et al ., ; Shubina et al ., ). In plants, one of the fibrillarin proteins, FIBRILLARIN 2 (FIB2), has been found in association with the RNA Polymerase II transcription mediator complex as subunit 36a (Bäckström et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Fibrillarin has also been shown to methylate glutamine residue 104 of the human histone H2A, weakening its binding to the FACT (facilitator of chromatin transcription) complex and impacting chromatin remodelling and rDNA transcription by RNA Pol I (Tessarz et al 2013), which points at an additional role for fibrillarin in ribosome biogenesis and translation. Fibrillarin itself is methylated on several arginine residues by protein arginine N-methyltransferase 1 (PRMT1), which is thought to influence its activity (Rodriguez-Corona et al 2015). Expression levels of fibrillarin have been shown to be regulated by p53 through direct binding to fibrillarin intron 1.…”
Section: Fibrillarin and Its Role In Henipavirus Infectionmentioning
confidence: 99%
“…X-ray data have suggested that the methylation of rRNA requires the formation of this complex with involvement of four fibrillarin molecules interacting with different regions of the target rRNAs. The yeast equivalent of fibrillarin, NOP1, has been more extensively studied than the human counterpart but fibrillarin is a well-conserved protein in most organisms, reinforcing the notion that all post-transcriptional processes involving fibrillarin such as chemical modification (methylation) of rRNA, pre-rRNA cleavage and ribosome assembly are essential for proper cellular functioning (Rodriguez-Corona et al 2015).…”
Section: Fibrillarin and Its Role In Henipavirus Infectionmentioning
confidence: 99%